Pengaruh Latihan Circuit Training Terhadap Kapasitas Aerobik Pada Siswa Ekstrakurikuler Bola Voli Di Smpn 21 Kota Bengkulu - Reno Charles; Roni Syahputra; Aziiz Rahman Putra (Educative Sportive, 2026)
This study aimed to determine the effect of circuit training on improving aerobic capacity (VO₂Max). The research employed an experimental method using a One-Group Pretest–Posttest Design. The population consisted of 20 students, all of whom were selected as the research sample through a total sampling technique. The instrument used in this study was an aerobic capacity test to measure VO₂Max before and after the implementation of the circuit training program. The training program was conducted over eight sessions, with training intensity gradually progressing through the adaptation, development, and intensive phases. The circuit training consisted of ten exercise stations: squat jumps, push-ups, sit-ups, back-ups, knee tuck jumps, back-ups with leg raises, squat thrusts, supine leg raises, trunk lifts, and running in place/skipping. The results showed an improvement in aerobic capacity following the circuit training program. The mean pre-test score was 10.63, while the mean post-test score was 9.68, indicating improved performance after eight training sessions. Based on the findings and discussion, it can be concluded that circuit training had a significant effect on the aerobic capacity of volleyball extracurricular students at SMP Negeri 21 Bengkulu City. This was evidenced by the t-test results, where the calculated t-value (5.214) was greater than the critical t-value (1.729) at a significance level of α = 0.05. Furthermore, the average post-test result was better than the pre-test result, indicating an increase in students’ aerobic capacity after participating in the circuit training program. Therefore, circuit training can be considered an effective training method for improving students’ aerobic capacity and cardiorespiratory endurance.